THE EFFECT OF DATE FRUITS (PHOENIX DACTYLIFERA L) INTERVENTION TO INCREASE HEMOGLOBIN LEVELS IN FEMALE ADOLESCENTS - Fathimah Fathimah; Vina Intan Aprilia; Kartika Pibriyanti; Lulu' Luthfiya; Hafidhotun Nabawiyah (Balai Penelitian dan Pengembangan Kesehatan Magelang, 2022)
Background. Anemia is one of the common health problems globally, where a condition of red blood cells is inadequate to meet the physiological needs caused by iron deficiency. The short term impact of anemia on adolescents can cause growth disorders, while the long term impact on pregnant women can cause pregnancy and childbirth complications. Date fruit is one of the fruits that containing iron (Fe), vitamin C, vitamin B complex, and folic acid that can help form red blood cells. Consuming the date fruits may improve formation of red blood cells and prevent anemia. Objective. To determine the effect of the intervention of date fruits in increasing hemoglobin levels among female adolescents at Islamic boarding school. Method. This research was performed using a pre-experimental study with one group pretest and posttest design. The sampling method in this research used purposive sampling with samples of 30 female adolescent students aged 15–18 years old at Modern Islamic Boarding School (Pondok Modern Gontor Putri 2), Ngawi, East Java, Indonesia. The inclusion criteria was adolescent suffering from anemia (age 15 until 18 years, Hb <12 g/dL, not menstruation during intervention). The intervention was carried out for seven days by giving seven date fruits (50 g) per day. Hemoglobin levels had recorded before and after intervention. The data were analyzed using paired t-test. Results. The median hemoglobin (Hb) level before giving date fruits was 10.8 g/dL and the median Hb level after giving date fruits was 11.9 g/dL. There were differences in Hb levels before and after giving date fruit in the treatment group (p=0.001). Conclusion. The intervention of consuming seven date fruits (50 g) for seven days effectively increased hemoglobin level.